Structural Insights on the SARS-CoV-2 Variants of Concern Spike Glycoprotein: A Computational Study With Possible Clinical Implications - Cueno, Marni E.; Imai, Kenichi (Frontiers in Genetics, 2021)
Coronavirus disease 2019 (COVID-19) pandemic has been attributed to SARS-CoV-2 (SARS2) and, consequently, SARS2 has evolved into multiple SARS2 variants driving subsequent waves of infections. In particular, variants of concern (VOC) were identified to have both increased transmissibility and virulence ascribable to mutational changes occurring within the spike protein resulting to modifications in the protein structural orientation which in-turn may affect viral pathogenesis. However, this was never fully elucidated. Here, we generated spike models of endemic HCoVs (HCoV 229E, HCoV OC43, HCoV NL63, HCoV HKU1, SARS CoV, MERS CoV), original SARS2, and VOC (alpha, beta, gamma, delta). Model quality check, structural superimposition, and structural comparison based on RMSD values, TM scores, and contact mapping were all performed. We found that: (1) structural comparison between the original SARS2 and VOC whole spike protein model have minor structural differences (TM>0.98); (2) the whole VOC spike models putatively have higher structural similarity (TM>0.70) to spike models from endemic HCoVs coming from the same phylogenetic cluster; (3) original SARS2 S1-CTD and S1-NTD models are structurally comparable to VOC S1-CTD (TM=1.0) and S1-NTD (TM>0.96); and (4) endemic HCoV S1-CTD and S1-NTD models are structurally comparable to VOC S1-CTD (TM>0.70) and S1-NTD (TM>0.70) models belonging to the same phylogenetic cluster. Overall, we propose that structural similarities (possibly ascribable to similar conformational epitopes) may help determine immune cross-reactivity, whereas, structural differences (possibly associated with varying conformational epitopes) may lead to viral infection (either reinfection or breakthrough infection).